Association of nocturia with cardiovascular and all-cause mortality: a prospective cohort study with up to 31 years of follow-up - Chen, Min; He, Wangan; Cai, Shaoqian; Chen, Zhi; Ye, Huarong; Jin, Zhigang; Lv, Xuexiang (Frontiers in Public Health, 2023)
Background Nocturia is a highly prevalent and under-considered condition and impacts the quality of life for many individuals. The long-term impact of nocturnal voiding on mortality, especially mortality from cardiovascular disease, remains unknown. The current study aimed to evaluate the relationship of nocturnal voiding episodes with cardiovascular and all-cause mortality among adults in the United States. Methods This is a prospective cohort study of a nationally representative sample of 13,862 U.S. adults aged 20 years or older who participated in the National Health and Nutrition Examination Survey III (1988–1994). Nighttime urination frequency was reported during an in-house interview. All-cause and cause-specific mortality were ascertained by linking to National Death Index mortality data through December 31, 2019. The associations of nocturia with cardiovascular and all-cause mortality were estimated using weighted Cox proportional hazards regression models. Results Throughout a median follow-up of 26.7 years, 5,029 deaths were reported, comprising 1,720 deaths from cardiovascular disease. In the fully adjusted model, participants who reported once, twice, and three or more times nocturnal voiding episodes have a higher risk of cardiovascular mortality (HR1, 1.22 [95% CI, 0.997–1.49], HR2, 1.47 [95% CI, 1.13–1.91], and HR ≥ 3, 1.96 [95% CI, 1.52–2.53]) as well as all-cause mortality (HR1, 1.12 [95% CI, 0.90–1.39], HR2, 1.54 [95% CI, 1.23–1.93], and HR ≥ 3, 2.48 [95% CI, 1.81–3.40]), compared to those without nocturia, and heart disease-specific mortality (HR1, 1.33 [95% CI, 1.08–1.64], HR2, 1.62 [95% CI, 1.25–2.10], and HR≥3, 2.07 [95% CI, 1.61–2.67]). Nevertheless, there was no significant relationship between the number of nocturia episode changes and stroke-specific mortality. Conclusion Nocturia was associated with a significantly augmented risk of overall and heart disease-specific mortality in a dosage-dependent manner. Early recognition and taking precautions may benefit individuals with nocturia by promoting quality of life and cardiac health.